Do Consumers Buy Impulsively More Often in Mobile Shopping Than in Store? - Wang, Lili (Auckland University of Technology, 2016)
This research focuses on identifying the similarities and differences in consumer motivation for impulse purchase between in-store and mobile shopping settings. Prior research has primarily focused on investigating brick-and-mortar or mobile impulse buying behaviour. However, what happens when consumers encounter opportunities to shop without planning via fast developing mobile shopping settings? Psychological variables such as materialism, time and money available, and immediate positive feelings are potential moderators of the relationship between consumer impulse purchase behaviour and the two settings.
Keywords: Impulse behaviour; Shopping patterns; Quantitative Research; Online shopping; In-store shopping